Development of candy sorting machine - Hazizan, Hairul Ikhwan; Rusli, Ahmad Najmie (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project focuses on the development of a candy sorting machine designed to automate the process of sorting candies based on color detection. With the increasing demand for efficiency in production, manual sorting can be time-consuming and prone to errors. The proposed machine aims to overcome these challenges by automatically sorting candies according to their colors. The primary goal of the project is to achieve precise color detection, uniform distribution, and effective sorting through the use of Arduino-based control. The design of the system includes an Arduino microcontroller, color sensors for detection, motors for sorting, and a mechanism to handle the sorted candies. The project also involves developing custom Arduino code to manage the color detection process, sorting algorithm, and control mechanisms. The expected outcome is a fully operational candy sorting machine capable of accurately sorting candies by color, significantly enhancing productivity and reducing the reliance on manual sorting processes. By automating the sorting procedure, the machine aims to improve efficiency in the candy production process.